IMPLEMENTASI TEORI BELAJAR BEHAVIORISME IVAN PETROVICH PAVLOV DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 GEDANGAN - Almas Sharfina 'Alaniah; Rokhmatul Khoiro Amin Putri; Siti Khorriyatul Khotimah (Universitas Islam Lamongan, 2023)
This study aims to describe the application of classical conditioning theory (Ivan Petrovich Pavlov's behaviorism learning) in Islamic Religious Education learning at SMA Negeri 1 Gedangan. This study uses a field research approach, in which researchers make observations in the field to collect data on an incident in scientific circumstances and collect correct, authentic data in the field. The data collection technique is through interviews with PAI subject teachers and observation at SMA Negeri 1 Gedangan. The results of the study explain that the implementation of classical conditioning theory in PAI learning has several things done by PAI teachers, namely by designing a visual learning process with various methods, namely peer tutoring, discussions, presentations, and group assignments that are applied so that students feel happy during the learning process. PAI teachers, in the process of teaching, ask students to take turns memorizing letters or hadiths, which they will then study in front of the class. After the students finished their memorization, the teacher gave appreciation with a smile and said